On the interval zoro symmetric single step procedure IZSS2-5D for simultaneous bounding of simple polynomial zeros - Jamaludin, Noraini; Monsi, Mansor; Hassan, Nasruddin (Hikari Ltd, 2013)
A new method called the interval zoro symmetric single-step procedure IZSS2-5D which is an extension of the previous procedure IZSS2 is described. The numerical results using five test polynomials contributed to shorter CPU times and reduced number of iterations.